Exploring the acceptance of fintech-based credit services: The impact of technology perception, social norms, and income - Indriani, Siska; Nurwati, Solikah; Mahrita, Ani (JSM: Jurnal Sains Manajemen, 2025)
The rapid growth of financial technology (fintech) has significantly changed how people access financial services, particularly through online lending platforms. In Indonesia, the adoption of online loans continues to rise, including in secondary cities such as Palangka Raya. However, despite their increasing popularity, concerns remain about their long-term use, risks of default, and behavioral determinants behind their adoption. This study aims to examine the influence of perceived ease of use of technology, social influence, and income on the interest in using fintech-based credit services among the urban community in Palangka Raya City. The research used a quantitative method with data collected from 96 respondents who had previously used online loan services. The data were analyzed using multiple linear regression after fulfilling classical assumption tests including normality, linearity, multicollinearity, and homoscedasticity. The results revealed that perceived ease of use and social influence had a significant and positive effect on interest in using online loans. Meanwhile, income was found to have no significant effect, suggesting that technological accessibility and social encouragement play a stronger role in determining adoption behavior than economic factors. These findings imply that fintech providers should focus on enhancing user interface simplicity and leveraging social influence through peer networks and influencers. Policymakers and financial regulators are recommended to promote financial literacy programs and ensure the legality of lending platforms to mitigate risks of over-indebtedness. Future research should consider integrating psychological and contextual factors such as trust, perceived risk, and digital literacy to deepen understanding of online lending adoption patterns. This study contributes to the literature on fintech acceptance and provides insights for inclusive and responsible financial innovation in emerging markets.